(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Public libraries increasingly function as inclusive public spaces that provide not only access to information but also a supportive environment for young users. This study analyzes how inclusive library facilities, services, and environments support the emotional comfort of Generation Z users at the Medan City Library and Archives Agency. A qualitative approach with a case study design was employed. Data were collected through observation, semi-structured interviews with Generation Z users, librarians, and library administrators, as well as document analysis. The data were analyzed thematically to identify patterns in user experiences and perceptions. The results indicate that inclusive facilities, accessible services, supportive interactions with librarians, and flexible study spaces contribute to users’ emotional comfort by fostering a sense of safety, acceptance, and belonging. The findings also reveal that Generation Z views the library as an inclusive public space offering a comfortable environment for studying, socializing, and engaging in individual activities. The study concludes that the inclusive practices implemented by the library support the emotional comfort of Generation Z users and reinforce the library’s role as an inclusive public space